Purification and properties of an alanine aminopeptidase from camel liver - Hassan Mohamed Masoud, Doaa Abdel-Khalek Darwish, Mohamed Salah-Eldin Helmy, Mohamed Mosaad Abdel-Monsef (Journal of Applied Pharmaceutical Science, 2017)
Alanine aminopeptidase is purified from camel liver to homogeneity and designated CLAAP. The purification procedure involved anion exchange chromatography on DEAE-cellulose column and gel filtration chromatography on Sephacryl S-300 column. The specific activity of CLAAP is increased to 9.9 folds over the crude extract with 25.3% yields. The purified CLAAP is homotrimmer protein with 180 kDa consists of three identical subunits of 60 kDa each. CLAAP displayed its optimum activity at pH 8.0 and the Km value is 0.083 mM alanine β-naphthylamide. The divalent cations CuCl2, MnCl2 and ZnCl2 inhibited CLAAP activity while CoCl2 and MgCl2 increased its activity. CLAAP was inhibited competitively with bestatin that has one binding site on the enzyme and Ki value of 14 µM. This report represents AAP purified from the camel liver as a safe source. Therefore, a task for the future will be the application of this purified CLAAP enzyme in the industry of meat and dairy products for flavor development.
Keywords: Alanine aminopeptidase,Camel liver, Purification, Characterization.